Research on the Establishment and Stability of the Beijing-Tianjin-Hebei Region Air Pollution Cooperative Control Alliance: An Evolutionary Game Approach - Wei. Zhu; Shaonan. Shan; Xiaohui. Shi; Hui. Li (Discrete Dynamics in Nature and Society)
Air pollution control refers to a vital issue in the integrated and coordinated development of the Beijing-Tianjin-Hebei region. As impacted by the fluidity of air pollution, air pollution control cannot be achieved independently by a single local government in the Beijing-Tianjin-Hebei region, and a long-term mechanism should be established for regional coordination and cooperative control. However, in the pursuit of maximising benefits by the participating parties, difficulties in effective coordination between the various control bodies occurred and a dilemma was created in the cooperative control of air pollution in the Beijing-Tianjin-Hebei region. Based on the existing research, this study first builds an evolutionary game model to analyse the evolutionary path and stability of cooperative alliance of air pollution control behaviour in the Beijing-Tianjin-Hebei region. Second, this study explores the core elements of reaching alliances and consolidating cooperative control among cities in the Beijing-Tianjin-Hebei region. Last, in combination with the simulation results, this study compares the feasibility of cooperative control among cities in the Beijing-Tianjin-Hebei region with and without central government constraints. As indicated from the results, without the constraints of the central government, intergovernmental cooperative control is correlated with intercity public benefits, cities’ own benefits, and air pollution losses, whereas it is not effective since it cannot control the phenomenon of “free-riding” by cities in the Beijing-Tianjin-Hebei region. Under the control of the central government, a stable strategy among cities can evolve toward a fast and efficient cooperative management. To achieve air pollution control effectively, the air pollution control alliance should be formed in the Beijing-Tianjin-Hebei region, and the benefits of cooperation lay the basis for reaching cooperative control. The mentioned findings highlight that (1) the benefits of cooperation lay the basis for cooperative control, (2) punitive policies of central government increase the evolutionary rate of cooperative control, and (3) cooperation costs determine the long-term stability of the alliance.